The Queer Racing of Children in Dionne Brand’s What We All Long For - Blair, Jennifer (Studies in Canadian Literature / Études en littérature canadienne)

(untitled) (The University of New Brunswick, 2012)
In Dionne Brand’s What We All Long For, race and queerness function together within a normative construction of time. The child/adult spectrum, which is also the innocence/experience spectrum, is portrayed as a racist and homophobic social convention that – along with the imagination of a particular future into which the child will mature – restricts the experiences and maturation potential of immigrant and racialized children in Canada. Brand’s text critiques this assumption that the future can be imagined, and alternative conceptions of time appear in several forms, from the characters’ own embodiments of time as they leave (or refuse to leave) childhood behind, to the recurrence of anachronistic figures (specifically the ghost and the baby-faced adult), to the ending with its compellingly negative representation of the future of the novel’s youth. Ultimately, the desiring child stands not for the affirmable future but for our inability to know what happens next – or what will come to constitute the human and the political realm in this “next.” This condition of unknowing precludes the possibility of determining – and placing limits upon – types of people.